Processo de internacionalização da Totvs: um estudo de caso da aquisição da mexicana Sipros - Brunhara, Aldo José (2009)
This work investigates how an acquisition can contribute to the internationalization strategy of one organization, having as a case study the acquisition of Sipros, a Mexican company, in 2003, by Totvs S.A, a Brazilian management software company and its internationalization process. This study includes a chronological study of Totvs internationalization process, the marketing data of ERP (Enterprise Resource Planning) management software segment for Brazil, Latin America and worldwide market and field researches including semi structured interviews with key people of the internationalization process of Totvs. The results of this research demonstrate that the main motivators for the acquisition were: interests on Sipros product line and customers base, the potential of the Mexican market, and evidences that the experience in Argentina had contributed to capture clients, Brazilian or foreign companies. Among the main contribution of this acquisition, it can be highlighted the learning process of the management of cultural differences and some faced difficulties related to the idioms and the local market needs, evolved the Mexican unit from one franchisee to a subsidiary, which contribute to develop products and provide services to other Spanish language countries such as Argentina, additionally, it motivated various organization adjusts at the headquarters structure aiming to have the best structure to support the activities abroad. Therefore, it can be emphasized that the acquisition of Sipros contributed to enlarge Totvs company s internationalization process and strategy, increasing the headquarters knowledge on how to manage the requirements to entry on markets with differences on culture and idioms